(untitled) (International Journal of Studies in Nursing, 2020)
Breast engorgement is а common issue affecting breastfeeding initiation and length. There are minimal options for relieving the pain associated with breast engorgement. Therefore, further study of strategies to achieve successful pain relief is crucial to promoting progress in breastfeeding. This study was conducted to evaluate and compare the effectiveness of compressed cold cabbage leaves versus hot compresses among postnatal mothers in relieving breast engorgement. Αn interventional quasi-experimental study design used to conduct this study. The study was carried out in the postnatal wards of Ismailia & port-Said general hospitals, and Suez Canal University Hospital. Α convenient sample study was 60 breast-engorgement postnatal mothers. Tools of data collection were; an interviewing questionnaire sheet included socio-demographic and obstetrical data, Visual Analogue Scale, and Six-point engorgement scale. The results showed that before the intervention, there was no statistically significant difference between the two groups linked to breast engorgement symptoms & body temperature. But body temperature, scores of breast engorgement and pain were statistically significant differentiated between the two groups’ pre and post-intervention. Significant improvement in the breast engorgement and pain scales after the intervention was found, (p < 0.001). In conclusion, this study revealed that hot compresses and cabbage leaves compresses, as well, for relieving breast engorgement; are time-efficient and easy to perform. However, hot compresses are better than compresses of raw cabbage leaves to minimize discomfort among postnatal mothers and to alleviate breast engorgement. Additional randomized controlled trials with potential placebo treatment should be performed to elucidate the unspecific effects of the application of hot compress and cold Cabbage leaves.